2019
DOI: 10.1021/jacs.8b13894
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photocatalytic Roles of Light: Charge Separation at the Band Gap and Heat via Localized Surface Plasmon Resonance To Convert CO2 into CO over Silver–Zirconium Oxide

Abstract: Confirmation of 13CO2 photoconversion into a 13C-product is crucial to produce solar fuel. However, the total reactant and charge flow during the reaction is complex; therefore, the role of light during this reaction needs clarification. Here, we chose Ag–ZrO2 photocatalysts because beginning from adventitious C, negligible products are formed using them. The reactants, products, and intermediates at the surface were monitored via gas chromatography–mass spectrometry and FTIR, whereas the temperature of Ag was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 64 publications
8
83
0
Order By: Relevance
“…This peak was significantly suppressed after 10‐min light irradiation, indicating the increased Debye–Waller factor (σ) value and the increased temperature (Figure 5; Figure S21 and Table S2, Supporting Information). [ 18 ] By contrast, the EXAFS spectrum of Co@SiO 2 exhibited a less obvious drop of the peak intensity after turning on the light, which was an indication of its lower local temperature under the illumination (Figure 5b). Moreover, the peak intensity returned to the original state for both samples after turning off the light, which was consistent with the light‐induced increase of local temperature of catalysts.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…This peak was significantly suppressed after 10‐min light irradiation, indicating the increased Debye–Waller factor (σ) value and the increased temperature (Figure 5; Figure S21 and Table S2, Supporting Information). [ 18 ] By contrast, the EXAFS spectrum of Co@SiO 2 exhibited a less obvious drop of the peak intensity after turning on the light, which was an indication of its lower local temperature under the illumination (Figure 5b). Moreover, the peak intensity returned to the original state for both samples after turning off the light, which was consistent with the light‐induced increase of local temperature of catalysts.…”
Section: Figurementioning
confidence: 95%
“…As suggested in a recent study, the increased Debye–Waller factor typically showed a decreased peak intensity in the EXAFS spectrum. [ 18 ] A main peak at 2.2 Å corresponding to metallic CoCo bonds was observed in the EXAFS spectrum of Co‐PS@SiO 2 ( Figure a). This peak was significantly suppressed after 10‐min light irradiation, indicating the increased Debye–Waller factor (σ) value and the increased temperature (Figure 5; Figure S21 and Table S2, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…The LSPR of Ag PNPs can create a local heat that assists the CO 2 photoreduction. Zhang and colleagues showed that, for CO 2 photoreduction in the presence of H 2 on Ag‐loaded ZrO 2 (Ag–ZrO 2 ) as photocatalyst, the local heat created by the LSPR of Ag NPs effectively activated H 2 to form H species, which were supplied to the CO 2 reduction on ZrO 2 surface sites . CO was efficiently generated at a rate of 0.66 μmol g −1 h −1 with approximately zero‐order kinetics.…”
Section: Plasmonic Photocatalysts For the Sunlight‐driven Conversion mentioning
confidence: 99%
“…thermal, "hot electron" or redox). [2][3][4][5][6][7] The mechanism of the Ullmann reaction is a subject of much debate, and different mechanisms have been proposed in the literature, depending on whether the catalysis is heterogeneous or homogeneous, and whether assisted by light. [8][9][10][11][12][13][14][15] The most commonly described mechanisms for this reaction are a classical catalytic oxidation pathway and reductive elimination, or a radical pathway.…”
Section: Introductionmentioning
confidence: 99%